Interleukin (IL)‐17F and IL‐17E are related to fibrosis and vasculopathy in systemic sclerosis. Issue 11 (19th July 2020) - Fukayama, Maiko; Yoshizaki, Ayumi; Fukasawa, Takemichi; Ebata, Satoshi; Kuzumi, Ai; Yoshizaki‐Ogawa, Asako; Asano, Yoshihide; Oba, Koji; Sato, Shinichi
Abstract: Systemic sclerosis (SSc) is an autoimmune disease that causes fibrosis and vasculopathy of the skin and internal organs against a background of autoimmune abnormalities. In recent years, the importance of the interleukin (IL)‐17 family for inflammatory diseases has received much attention, but autoimmune diseases have not yet been fully explored. As for SSc, there is also no unified perspective on the involvement of the IL‐17 family in its development, and few studies have been conducted linking IL‐17F and IL‐17E particularly to the disease severity. In the present study, we examined the correlation between serum IL‐17F and IL‐17E levels and disease severity in SSc patients. Moreover, the expression of the receptors for these cytokines, IL‐17RB and IL‐17RC, in skin tissues obtained by skin biopsy was examined by immunohistochemistry. Both cytokines were significantly elevated in the sera of patients with diffuse cutaneous SSc patients compared with healthy controls. Serum IL‐17F levels correlated with modified Rodnan total skin thickness score, a semiquantitative measure of skin sclerosis, percent predicted forced vital capacity, percent predicted carbon monoxide lung diffusion capacity and serum levels of Krebs von den Lungen‐6 and surfactant protein‐D, serological markers of interstitial lung disease. Serum IL‐17E levels were significantly correlated with percent predicted forced vital capacity and serum Krebs von den Lungen‐6 levels. Serum levels of IL‐17F and IL‐17E also correlated with the prevalence of digital ulcers, and serum IL‐17F levels were associated with elevated right ventricle systolic pressure values. In addition, IL‐17RC and IL‐17RB expression was increased in the skin tissues of diffuse cutaneous SSc patients. These results suggested that IL‐17F and IL‐17E could be involved in fibrosis and vasculopathy in SSc through their respective receptors in the affected organ tissues.